Analisis Luas Penampang dan Pengaruh Jarak Terhadap Transmisi Daya pada Wireless Charger Universal Smartphone - Very Bagus Saputra; Cahyo Kumolo; Nur Fahmi Fauziati Wibowo (Khazanah Informatika, 2016)
Wireless technology is the development of technology that is needed currently given the technological advances in electronic devices very rapidly. Every electronic devices certainly require electric power and cable as the conductor. Therefore, if there is a tool that can transfer electric power without wires, it would be more easy for the user to use the electronic devices. Transfer of electrical energy wireless has several advantages over using a cable that can increase comfort in the use of electrical equipment and can reduce the amount of electronic waste. . The method used for wireless energy transfer in this paper uses an resonance techniques inductive electromagnetic field. User create two shaped copper solenoid coils used to generate the mutual inductance. Wireless electrical energy transfer circuit consists of two circuits that the transmitter and receiver circuit. Transmitter circuit consists of a series LC oscillation and receiver circuit is a merger several electronic components. Realization tool works well with setting the appropriate components. However, the effect of distance between the coil greatly affect the value of the electricity that is able to be transferred. The test results showed that the receiver coil sectional area of 2.5 mm2 be able to receive a maximum power of 1.36 watts and the farthest distance of 12 cm. So, the farther away the distance between the coils, the smaller energy capable to be transfer.